O ensino da Matemática nos anos iniciais do Ensino Fundamental: implicações das políticas de alfabetização - Eduardo de Almeida Andrade (2016)
The research described in this master's dissertation in education aims to investigate the implications of public policies to promote reading and writing on the teaching of mathematics in the early years of elementary school. The study has its origin in concerns arising from the unsatisfactory levels of mathematics achievement in this phase of elementary schooling, as revealed by large-scale external assessment. In addition, interest in the proposed topic was also based on results from the GERES Research Project (Longitudinal Study of School Generation 2005) that showed a fall in the rate of growth in performance at the end of the first three years of elementary education in public schools. The participants in the present study are teachers in the early years of elementary school of the Municipal Education System of Teixeira de Freitas, Bahia. To carry out the research, we adopted a primarily quantitative approach with the use of interview and questionnaire. The theoretical foundation comes from the contributions of authors who discuss public policies, external evaluations and the teaching of mathematics. On the basis of the results, it was observed that teachers give importance to external evaluations as tools to point out what needs to be improved in relation to the students´ performance and help guide the planning of educational activities. However, with regard to public literacy policies, it was found that teachers give priority to reading and writing at the expense of mathematics teaching. This research exposes the urgent need that teachers and administrators make sufficient and effective investment in the early years of elementary school, specifically in mathematics teaching. This is research that will contribute to strengthening the production of knowledge in the field of education, in particular for the teaching of mathematics and the growth of the debate on childrens right to a quality education, based on global and not segmented knowledge.